2013
DOI: 10.1105/tpc.112.105049
|View full text |Cite
|
Sign up to set email alerts
|

Nitrated Cyclic GMP Modulates Guard Cell Signaling inArabidopsis 

Abstract: Nitric oxide (NO) is a ubiquitous signaling molecule involved in diverse physiological processes, including plant senescence and stomatal closure. The NO and cyclic GMP (cGMP) cascade is the main NO signaling pathway in animals, but whether this pathway operates in plant cells, and the mechanisms of its action, remain unclear. Here, we assessed the possibility that the nitrated cGMP derivative 8-nitro-cGMP functions in guard cell signaling. Mass spectrometry and immunocytochemical analyses showed that abscisic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
114
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 65 publications
3
114
0
1
Order By: Relevance
“…However, MYB44 also negatively regulates ABA responses (Jaradat et al, 2013;Li et al, 2014) involved in stomatal closure, leaf senescence, and ROS scavenging (Persak and Pitzschke, 2014). In our study, MYB44 expression correlated positively with glycerol levels and negatively with the expression of NOGC1, a nitric oxide-dependent guanylyl cyclase involved in stomatal closure via Ca 2+ signaling (Mulaudzi et al, 2011;Joudoi et al, 2013). In addition, MYB44 correlated positively (r = 0.85, P = 0.001) with the chloroplastic lipid transfer protein LTPc1 (At2g10940), which together with LTPc2 (At2g45180) was up-regulated during O 3 stress but not herbivore stress (Supplemental Figs.…”
Section: Effects Of O 3 Stress On Photosynthesis and Stomatal Regulationmentioning
confidence: 53%
“…However, MYB44 also negatively regulates ABA responses (Jaradat et al, 2013;Li et al, 2014) involved in stomatal closure, leaf senescence, and ROS scavenging (Persak and Pitzschke, 2014). In our study, MYB44 expression correlated positively with glycerol levels and negatively with the expression of NOGC1, a nitric oxide-dependent guanylyl cyclase involved in stomatal closure via Ca 2+ signaling (Mulaudzi et al, 2011;Joudoi et al, 2013). In addition, MYB44 correlated positively (r = 0.85, P = 0.001) with the chloroplastic lipid transfer protein LTPc1 (At2g10940), which together with LTPc2 (At2g45180) was up-regulated during O 3 stress but not herbivore stress (Supplemental Figs.…”
Section: Effects Of O 3 Stress On Photosynthesis and Stomatal Regulationmentioning
confidence: 53%
“…3) (21). On the other hand, several studies have found a positive role of exogenous application of NO in ABA-induced stomatal closure (15,20,22,24). Exogenous NO might promote stomatal closure by regulating ion channels (20,23), or by generating nitrated cGMP (24).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous NO might promote stomatal closure by regulating ion channels (20,23), or by generating nitrated cGMP (24). Alternatively, the observed positive role of exogenous NO on ABA responses in guard cells might be caused by secondary effects, such as induction of ROS or other second messengers (24,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5) We discovered endogenous formation of the nitrated cGMP derivative 8-nitroguanosine 3′,5′-cyclic monophosphate (8-nitro-cGMP) under conditions associated with excess production of both nitric oxide (NO) and reactive oxygen species in mammalian cells [7][8][9][10][11][12][13][14][15][16][17] as well as in plants. 18,19) Biochemical analyses revealed that 8-nitro-cGMP can activate PKG1α to a similar extent as native cGMP can. 9,12) Although native cGMP is degraded by phosphodiesterase to form guanosine 5′-mono-phosphate, 8-nitro-cGMP was resistant to phosphodiesterasemediated degradation.…”
mentioning
confidence: 99%